Association between blood pressure and circadian timing of physical activity of Japanese workers - Imamura, Momoko; Tahara, Yu; Suiko, Takahiko; Nagamori, Yuki; Shibata, Shigenobu (Frontiers in Physiology, 2022)
High blood pressure (BP) is reported to be accounted for more than 10 million deaths and the high prevalence of hypertension is a global issue. Exercise is known to reduce BP and the optimal exercise prescription has been discussed. Furthermore, since the circadian clock plays an important role in BP regulation and its related physiological functions, the time-of-the-day difference in the effect of exercise on BP is suggested. However, when people should regularly exercise for the prevention of hypertension remains unclear. In this cross-sectional research, we analyzed the association of habitual exercise and BP depending on their conducted timing in addition to the time length and frequency for three levels of intensity from an analysis of questionnaire answered by Japanese male workers (N = 2343, mean age ± SE = 49.2 ± 0.2 years old). Consistent with the previous research, correlation analysis revealed that frequency, time length, and weekly MET-minutes of total physical activities were negatively associated with SBP and DBP. Vigorous physical activity showed a time-specific negative association (06:00-09:00 PM) and walking in the early morning (03:00-06:00 AM) showed a positive association with SBP and DBP. Multiple regression analysis, eliminating the confounding factors such as age and BMI, confirmed these results. When participants were divided into groups according to their BP, compared to normal BP groups, higher BP groups exercised less in the evening. Our findings suggest that when to exercise is important, and that exercising in the evening (06:00-09:00 PM) may be better to achieve the hypotensive effect of exercise.